Muito antes da marca: relações entre a recepção de publicidade e o consumo de alimentos por crianças de classes populares - Paula, Fernanda Cintra de (2013)
The theme of this dissertation is childhood, communication and consumption. With a focus on the symbolic value of merchandise, it presents a study on the relationship between the exposure to advertising and consumption of food by children in working class families, thus enriching the debate about consumption directed at children in modern Brazilian society. The purpose of the study is to analyze meaning processes made by children in relation to appeals by the media (especially advertising) for the consumption of food products. Based on British Cultural Studies and on theories of communication, consumption culture and childhood culture; and using a methodology that includes field research of an ethnographic nature with observation of neighborhood and housing, identification of the television programming watched by the children, observation of commercial breaks most watched by children and identification of movements to prohibit advertising aimed at children, this study on exposure of working class children also examines questions related to regulation of advertising aimed at children.